Pengaruh Kualitas Produk, Citra Merek, dan Persepsi Hargaterhadap Keputusan Pembelian Konsumen di Kota Surabaya Pada Produk Viva Cosmetics - Izah Bana Murtazah; Ade Rishna Hidayah Shafira Buchori (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the influence of product quality, brand image, and price perception on purchasing decisions for Viva Cosmetics products in Surabaya. The background of this study is based on the increasingly fierce competition in the cosmetics industry and fluctuations in the Viva Cosmetics Top Brand Index, necessitating appropriate strategies to improve consumer purchasing decisions. This study used a quantitative method with a causal associative approach. The population in this study were consumers residing in Surabaya who had purchased Viva Cosmetics products, with a sample of 30 respondents selected using a purposive sampling technique. Data were collected through a Likert-based questionnaire and analyzed using multiple linear regression with SPSS 23. The results showed that product quality, brand image, and price perception, both partially and simultaneously, had a positive and significant influence on purchasing decisions. Partially, product quality had a significance value of 0.015, brand image 0.001, and price perception 0.004 (p < 0.05). Brand image was the variable with the most dominant influence on purchasing decisions. The coefficient of determination (R²) of 0.787 indicates that 78.7% of the variation in purchasing decisions can be explained by the three independent variables, while the remaining 21.3% is influenced by other variables outside the study. Therefore, improving product quality, strengthening a more modern brand image, and setting prices that align with consumer value perceptions can encourage increased purchasing decisions for Viva Cosmetics products in Surabaya.